Physical Health and Health Behaviours of Australians with Psychosis. - Happell, Brenda; Platania-Phung, Chris; Furness, Trentham; Scholz, Brett; Niyonsenga, Theo; Watkins, Andrew; Curtis, Jackie; Wang, Zijian; Khanijou, Supriya; Stanton, Robert (Community Mental Health Journal, 2025)
People living with psychosis live up to 20 years less compared to the general population. Cardiometabolic ill-health and barriers to health-related behaviour are significant contributors. This is a cross-sectional descriptive study of cardiometabolic health and health behaviours of consumers attending a public community mental health service in an Australian city. One hundred and fourteen consumers currently living with psychosis participated. Standard measures of cardiometabolic health, quality of life and, health-related behaviours were utilised. Data were analysed using descriptive statistics. The cohort reported higher fruit intake and physical activity, and lower excess alcohol use compared to previous studies. Health-related behaviours including smoking and vegetable intake were poorer than previously reported. Participants had low levels of cardiometabolic health (e.g. abnormal lipids). Physical and mental quality of life was also lower than for general populations. Improved efforts to address physical health for people with mental health conditions are urgently needed.